(untitled) (Fiep Bulletin - online, 2016)
The Education Distance is gaining prominence in the Brazilian educational scenario and the course of undergraduate physical education has been offered in this mode in order not only to train teachers but also to develop citizenship and quality of life and health promotion. Depending on the virtual teaching the use of computer technology resources and other instruments such as video and multimedia, it is increasingly possible to resolve issues related to the course that would be taken as foreclosing as the contact and the simulation of movements.